Proceedings of the Sixth International Workshop on Health Text Mining and Information Analysis 2015
DOI: 10.18653/v1/w15-2607
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact of Twitter-based Health Campaigns: A Cross-Country Analysis of Movember

Abstract: Health campaigns that aim to raise awareness and subsequently raise funds for research and treatment are commonplace. While many local campaigns exist, very few attract the attention of a global audience. One of those global campaigns is Movember, an annual campaign during the month of November, that is directed at men's health with special foci on cancer & mental health. Health campaigns routinely use social media portals to capture people's attention. Recently, researchers began to consider to what extent so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
8
1
2
Order By: Relevance
“…FH-related tweet content analysis revealed that during the study period, majority of tweets posted by both organizations and individuals were in the awareness/prevention category. This finding was in contrast to a previous study that reported Twitter users were more likely to tweet on social aspects of awareness campaigns rather than health aspects 5 . The highest number of daily tweets recorded in each month were associated with singular events, similar to a prior report that found tweets related to cardiology increased in response to news and events 2 .…”
contrasting
confidence: 99%
“…FH-related tweet content analysis revealed that during the study period, majority of tweets posted by both organizations and individuals were in the awareness/prevention category. This finding was in contrast to a previous study that reported Twitter users were more likely to tweet on social aspects of awareness campaigns rather than health aspects 5 . The highest number of daily tweets recorded in each month were associated with singular events, similar to a prior report that found tweets related to cardiology increased in response to news and events 2 .…”
contrasting
confidence: 99%
“…More recently, Robert (2013) analyzed health-related fundraisers that utilize temporary body modification with a focus on Movember and Julyna, while Wassersug, Oliffe, and Han (2015) compared Movember’s fundraising strategies with the history of prostate cancer awareness that typically relied on masculine stereotypes. Research at the intersection of Movember and use of social media is even more limited: Prasetyo, Hauff, Nguygen, van den Broek, and Hiemstra (2015) conducted a multi-country analysis of Movember to analyze the impact of tweets on donations, and Bravo and Hoffman-Goetz (2015) conducted a content analysis of 4,222 Canadian tweets to determine what topics were discussed on Twitter.…”
Section: Introductionmentioning
confidence: 99%
“…In our data, 382 users have only one relevant tweet and 1,271 users have 5 relevant tweets or less. Furthermore, many of the tweets posted during the campaign focus on the Movember community (Bravo and Hoffman-Goetz, 2015;Dwi Prasetyo et al, 2015), making it hard to distinguish between the different motivations. For example, instagram.com is among the top three of hostnames for all motivation types.…”
Section: Resultsmentioning
confidence: 99%